Ophthalmologic examination and ocular ultrasound of the south american coati (Nasua nasua) - Anita Marchionatti Pigatto; Guilherme Rech Cassanego; Carolina Cauduro da Rosa; Jean Carlos Gasparotto; Luiza Tonietto Mangini; Gabriella De Nardin Peixoto; Natália Karianne Brandenburg; Luís Felipe Dutra Corrêa; Alexandre Krause (Ciência Rural)
ABSTRACT: To determine species-specific reference values for ophthalmological tests is essential to diagnose ocular conditions. This study measured ophthalmological and ocular ultrasonographic parameters of the eye of captive coatis (Nasua nasua). Data obtained during the routine physical examination were from twelve coatis (24 eyes), two to five years old, five males and seven females, clinically healthy. Blood collection and ophthalmological evaluation using the Schirmer tear test 1 (STT 1), measurement of intraocular pressure (IOP) and central corneal thickness (CCT), ecobiometry (US) and indirect ophthalmoscopy were performed. The results were analyzed and compared using the Student T test (P < 0.05), according to eye (right and left) and sex. For the STT, the mean values (mean ± standard deviation) were 2.29 ± 0.85 mm/min, for IOP of 8.22 ± 1.97 mmHg and for CCT, of 324.29 ± 18.01 µm. Echo biometry measures were: 1.48 ± 0.08 mm for anterior chamber depth (ACD); 4.09 ± 0.09 mm for lens thickness (LT); 3.59 ± 0.18 mm for vitreous chamber depth (VCD), and 9.17 ± 0.18 mm for axial globe length (AGL). Retina showed a holangiotic vascular pattern with a broad tapetum and the presence of the optic disc. Statistical analysis did not show any difference between eyes (left or right) and gender for all parameters. The values obtained for CCT and US are not previously available in the literature, and together with STT, IOP and retinal pattern, can be used as reference for the species.